Highly variable salinity conditions at the Early Permian Mangrullo Formation (northeastern Uruguay): effects on the biota - Morosi, E. (2010)
The shales, mudstones and limestones of the Mangrullo Formation (Early Permian, northeastern Uruguay) were deposited in a water body which progressively closed its connection with the open sea, producing a gradual restriction of the basin and an increasing of the salinity by evaporation under arid conditions. This unit contains a peculiar biota, characterized by its low diversity and great abundance, attributes that became particularly evident at the time of highest restriction, when mesosaurs and pygocephalomorph crustaceans colonized the basin. At that time, a system of hypersaline lagoons could have been established, which is coherent with ecological, morphological and geological evidence. The increasing salinity could strongly affect the biota at the base of the unit, which probably lived under brackish to freshwater conditions. Thus, fishes, mollusks, conchostracans and bioturbating organisms become totally absent, just before the first mesosaurs appear. An extremely low diverse community dominated by two or at most three species joining mesosaurs, pygocephalomorphs, and the ichnofossil Chondrites (the "mesosaur community") substituted the fish-dominated biota. Mesosaurs and pygocephalomorphs developed adaptive structures (e.g., salt glands and marsupial chambers) to favor osmoregulation in such specialized environments. Evaporitic gypsum crystals around the fossils suggest seasonal drying, that along with evidence of nearest volcanic activity could have affected the components of the mesosaur community. They become extinct before a new fish-dominated biota appears at the upper mudstones of the unit, suggesting a reestablishment of the connection with the open sea.